2020
DOI: 10.1016/j.redox.2020.101637
|View full text |Cite|
|
Sign up to set email alerts
|

Substrate metabolism regulated by Sestrin2–mTORC1 alleviates pressure overload-induced cardiac hypertrophy in aged heart

Abstract: Sestrin2 (Sesn2) is a stress sensor for the mammalian target of rapamycin complex 1 (mTORC1) pathway. Aging impairs cardiac mTORC1 activation, thereby sensitizing the heart to hypertrophy. C57BL/6 J young wild-type (young WT; 4–6 months), aged WT (24–26 months), and young Sestrin2 knockout mice (Y-Sesn2 KO; 4–6 months) underwent transverse aortic constriction (TAC) for pressure overload. Cardiac expression of Sesn2 decreased with age. At 4 weeks after TAC, aged WT and Y-Sesn2 KO exhibited larger hearts and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
0
13
1
Order By: Relevance
“…Besides, Sestrin2 knockout led to increased fibrogenesis and development of more severe pressure overload cardiac remodeling and hypertrophy in rats [107]. Sestrin2 knockout disrupted mitochondrial function of cardiomyocytes and was associated with decreased glucose oxidation; decreased PGC-1α and mitochondrial DNA; and elevated levels of 4-hydroxynonenal, a lipid peroxidation byproduct, in the rat model of pressure overload-mediated heart failure [107]. Sestrin2 knockout decreased autophagy and increased apoptotic cell death of cardiomyocytes, as well [107].…”
Section: Myocardial Ischemia-reperfusion (Ir)mentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Sestrin2 knockout led to increased fibrogenesis and development of more severe pressure overload cardiac remodeling and hypertrophy in rats [107]. Sestrin2 knockout disrupted mitochondrial function of cardiomyocytes and was associated with decreased glucose oxidation; decreased PGC-1α and mitochondrial DNA; and elevated levels of 4-hydroxynonenal, a lipid peroxidation byproduct, in the rat model of pressure overload-mediated heart failure [107]. Sestrin2 knockout decreased autophagy and increased apoptotic cell death of cardiomyocytes, as well [107].…”
Section: Myocardial Ischemia-reperfusion (Ir)mentioning
confidence: 99%
“…Sestrin2 knockout disrupted mitochondrial function of cardiomyocytes and was associated with decreased glucose oxidation; decreased PGC-1α and mitochondrial DNA; and elevated levels of 4-hydroxynonenal, a lipid peroxidation byproduct, in the rat model of pressure overload-mediated heart failure [107]. Sestrin2 knockout decreased autophagy and increased apoptotic cell death of cardiomyocytes, as well [107].…”
Section: Myocardial Ischemia-reperfusion (Ir)mentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, sestrin2 knockdown was reported to aggravate the cardiomyocyte hypertrophy induced by phenylephrine, and sestrin2 overexpression protected cardiomyocytes from phenylephrine-induced hypertrophy, suggesting a protective effect of sestrin2 against cardiomyocyte hypertrophy [ 36 ]. In addition, Quan et al reported that sestrin2 knockout mice had larger hearts and impaired cardiac function after aortic constriction for pressure overload [ 51 ]. Hypertension is the main pathological factor in the development of heart failure, and heart failure caused by hypertension is characterized by cardiac hypertrophy.…”
Section: Sestrin2 and Cardiac Diseasesmentioning
confidence: 99%
“…Hypertension is the main pathological factor in the development of heart failure, and heart failure caused by hypertension is characterized by cardiac hypertrophy. An adeno-associated virus delivery of sestrin2 rescued the sestrin2 expression, attenuated the activation of mTORC1 and increased the pressure overload tolerance in hearts [ 51 ]. These results indicate that sestrin2 inhibits myocardial hypertrophy by inhibiting the mTORC1 pathway, thereby regulating protein synthesis, metabolism, autophagy, and apoptosis.…”
Section: Sestrin2 and Cardiac Diseasesmentioning
confidence: 99%